Young people from a migrant background : chances on the training market - Beicht, Ursula [Verfasser] (My University, 2017)
"The training market situation has significantly improved for young people over recent years. Has this led to bet-ter opportunities for young migrants to find a training place? The present article looks into this question via a consideration of the training place applicants registered with the Bundesagentur für Arbeit (BA) [Federal Employ-ment Agency] for the period from 2004 to 2014." (author's abtract ; BIBB-Doku)
Jugendliche mit Migrationshintergrund
Keywords: P 1.5 Migranten; G 1.3.1.1 Ausbildungsstellenmarkt; Jugendlicher; Migrant; Ausbildungschance; Ausbildungsstellenmarkt; Einmündungsquote